Benjamin Disraeli letters: 1815-1834 - Disraeli, Benjamin, 1804-1881 (Letters of Benjamin Disraeli., 1982)
This volume includes 363 letters (many previously unpublished) from€Benjamkin Disraeli's€school boy days to his establishment in the Tory camp under the patronage of Lord Lyndhurst. Most prominent are Disraeli's letters to his sister, Sarah, with whom he corresponded frequently over several decades.